Analysis Of The Influence Of Work Experience And Organisational Climate On Employee Performance, With Performance Benefits As An Intervening Variable In The Office Of Customs And Excise Supervision And Services - Rahmat Hidayat; Isa Indrawan; Kiki Farida Ferine (International Journal of Society and Law, 2024)
The research was conducted to see the influence of work experience and organizational climate on employee performance with performance allowances as an intervening variable at the Medan City Customs and Excise Supervision and Service Office. This research used a quantitative type of research. This research was carried out at the location where the research was carried out at the Medan City Customs and Excise Supervision and Service Office. The population used was 131 employees and the sampling technique used was the Slovin technique so that the sample used was 99 employees, the data collection technique used was questionnaire distribution, the research model used was analysis method and the measuring instrument used the Smart PLS version 3.0. The results of this research are as follows: Organizational climate has a positive and significant effect on employee performance with an original sample value of 0.568 and a p value of 0.000. Organizational climate has a positive and significant effect on performance allowances with a sample value of 0.792 and a p value of 0.000. Work Experience has a positive and insignificant effect on Employee Performance with an original sample value of 0.123 and a p value of 0.062. Work Experience has a positive and insignificant effect on Performance allowances with an original sample value of 0.154 and a p value of 0.093. Performance allowances have a positive and significant effect on employee performance with an original sample value of 0.295 and a p value of 0.001. Organizational climate has a positive and significant effect on employee performance through performance allowances with an original sample value of 0.234 and a p value of 0.002. Work Experience has a positive and insignificant effect on Employee Performance through performance allowances with an original sample value of 0.045 and a p value of 0.175.